Construction of PMoV/rGO/Pt nanocomposite with photoreduced graphene oxide for efficient quantification of vanillic acid - Shixu Chen; Na Li; Cong Zhang; Haiyan Zhao; Min Cui; Bao Sun (Polyoxometalates)
Polyoxometalates (POMs), as a unique type of metal–oxygen cluster compound, undergo multi-electron transfer while maintaining their structures. In this study, an electrochemical sensor that rapidly and sensitively detects vanillic acid was synthesized using vanadium-substituted POM (H4PMo11VO40, PMoV), reduced graphene oxide (rGO), and platinum (Pt) nanoparticles, where PMoV acted as both the photoreductant and stabilizer. In particular, PMoV/rGO/Pt composite was prepared and identified using various methods. Under optimal conditions, the limit of detection of the synthesized electrochemical sensor was estimated to be 0.9 μM at vanillic acid concentrations of 50–1350 μM. In addition, the practical application of PMoV/rGO/Pt/GCE (GCE = glassy carbon electrode) was considered by determining the concentration of vanillic acid in tap and lake water with good recovery (98.36%–102.11% and 97.11%–100.22%, respectively). The synthesized sensor realizes simple, rapid, and economical detection of vanillic acid and can serve as an important analytical tool in this direction.